Innovative research methodologies in the EU regulatory framework: an analysis of EMA qualification procedures from a pediatric perspective - Giannuzzi, Viviana; Bertolani, Arianna; Torretta, Silvia; Reggiardo, Giorgio; Toich, Eleonora; Bonifazi, Donato; Ceci, Adriana (Frontiers in Medicine, 2024)
Introduction. The European Medicines Agency (EMA) offers scientific advice to support the qualification procedure of novel methodologies, like preclinical and in vitro models, biomarkers, pharmacometric methods, to endorse their acceptability into medicines R&D. This is particularly relevant to overcome scarcity of data, lack of validated endpoints and biomarkers in research fields characterized by small samples, like pediatrics. Aim. To analyze the potential pediatric interest of methodologies qualified as “novel methodologies for medicine development” by the EMA. Methods. The positive qualification opinions of novel methodologies for medicine development published on the EMA website between 2008 and 2023 were identified. We performed multi-level analyses to investigate data with a hierarchical structure and the effects of cluster-level variables and cluster-level variances in order to evaluate their potential pediatric interest, defined as the possibility to use the novel methodology in pediatric R&D, and the availability of pediatric data. The duration of the procedure, the type of methodology, the specific disease or disease area addressed, the type of applicant, and the availability of pediatric data at the time of the opinion release, were also investigated. Results. Most of the 27 qualifications of novel methodologies issued by the EMA (70%) were potentially of interest for pediatric patients, but only 6 of them reported pediatric data. The overall duration of qualification procedures with pediatric interest was longer than the overall duration of procedures without any pediatric interest (median time 7.0 months vs. 3.5 months, respectively; p-value = 0.082). In parallel, qualification procedures which included pediatric data lasted a longer period of time (median time 8.0 months vs. 6 months, respectively; p-value = 0.150). Nephrology and neurology represented the main disease areas (21% and 16%, respectively). Endpoints, biomarkers and registries represented the main type of innovative methodologies (32%, 26%, and 16respectively). Discussion: Our results support the need for implementing innovative methodologies in regulatory-compliant pediatric research activities. Pediatric-dedicated research infrastructures providing regulatory support and strategic advice during research activities could be crucial to design ad hoc pediatric methodologies or to extend and validate them for pediatrics.